Analogy and Demonstration. Some Developments in the Medieval Tradition of Posterior Analytics (Doctor Virtualis, 2023)
The paper deals with the problem of predicative analogical connections in the Aristotelian theory of demonstration, where they are marginal, and with its developments in the thirteenth-century medieval latin exegetical tradition.Grosseteste claims that demonstration can prove predicates that are said analogically of different subjects; Kilwardby and, after him, even more Giles of Rome show that this aim can be reached also through a medium analogically connected to the extreme terms. Giles upholds in a passage the existence of a hierarchical order among properties analogically demonstrated; somewhere else, however, he shows that they can configure more variously.In the following century, John Buridan resumes the basic lines of those interpretations, in the framework of a general widening of the features of Aristotelian science; maybe, his ideas on analogy could represent an initial stage of this tendence.
Keywords: Theory of demonstration; Analogy; Posterior Analytics; Medieval exegetical tradition